“Todos los hombres nacieron en Jerusalém”. Mito y Evangelio en las narraciones sobre los orígenes de los humanos entre los toba (qom) del Chaco argentino - Tola, Florencia Carmen (2011)
Parallelisms between stories of biblical inspiration and myths that describe the origins of the human beings, their corporal transformations and the differences between diverse types of beings can be found in contemporary narrations of the Toba people (Qom) of the Argentinean Gran Chaco. Events described in the Bible are usually spun with elements of the mythical past of Toba people, therefore generating a biblical reading of the indigenous past and new readings on the human origins, of the differences between beings and of the importance of the body in the constitution of human specificity. This paper examines some of these narrations where myths and Biblical stories are interlaced giving rise to new notions of body and person.